Synthesis and In Vitro Evaluation of C-7 and C-8 Luteolin Derivatives as Influenza Endonuclease Inhibitors - Reiberger, Robert; Radilová, Kateřina; Kráľ, Michal; Zima, Václav; Majer, Pavel; Brynda, Jiří; Dračínský, Martin; Konvalinka, Jan; Kožíšek, Milan; Machara, Aleš (International journal of molecular sciences, 2021)
The part of the influenza polymerase PA subunit featuring endonuclease activity is a target for anti-influenza therapies, including the FDA-approved drug Xofluza. A general feature of endonuclease inhibitors is their ability to chelate Mg2+ or Mn2+ ions located in the enzyme's catalytic site. Previously, we screened a panel of flavonoids for PA inhibition and found luteolin and its C-glucoside orientin to be potent inhibitors. Through structural analysis, we identified the presence of a 3',4'-dihydroxyphenyl moiety as a crucial feature for sub-micromolar inhibitory activity. Here, we report results from a subsequent investigation exploring structural changes at the C-7 and C-8 positions of luteolin. Experimental IC50 values were determined by AlphaScreen technology. The most potent inhibitors were C-8 derivatives with inhibitory potencies comparable to that of luteolin. Bio-isosteric replacement of the C-7 hydroxyl moiety of luteolin led to a series of compounds with one-order-of-magnitude-lower inhibitory potencies. Using X-ray crystallography, we solved structures of the wild-type PA-N-terminal domain and its I38T mutant in complex with orientin at 1.9 Å and 2.2 Å resolution, respectively.
Keywords: Luteolin; Antiviral Agents; Catalytic Domain; Endonucleases; Mannich reaction; bio-isosterism; influenza; RNA polymerase; luteolin; cross-coupling; Orthomyxoviridae; katalytická doména; flavonoids; endonukleasy; endonuclease inhibitor; antivirové látky; Viral Proteins; virové proteiny